Kak pozhivaesh', Ufa? . Kak pozhivaesh', Ufa? . How Are You, Ufa? . Как поживаешь, Уфа? - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. An abandoned village in Bashkortostan; Tolkien fans of Bashkiria; the work of Bashkir tax police; people from Afghanistan, residing in Ufa; the opening of a small ice field in the Palace of Sport in Ufa; social service "Dobraya usluga" ("Kind Favor"), operating on the phone; interview with Konstantin Baurov, a collector of vinyl disks with gypsy romance singing. Contributors: Saitov, Azamat (Anchor); Tagirova, Irina (Anchor) Заброшенное село в Башкортостане; башкирские толкиенисты; работа башкирской налоговой полиции; уроженцы Афганистана, проживающие в Уфе; открытие малой ледовой арены в уфимском Дворце Спорта; телефонная социальная служба "Добрая услуга"; интервью с Константином Бауровым, собирателем пластинок с цыганскими романсами. Создатели: Саитов, Азамат (Ведущий/Ведущая); Тагирова, Ирина (Ведущий/Ведущая)